2021
DOI: 10.1136/openhrt-2020-001538
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the extent of myocardial damage in patients with STEMI using the DETERMINE score

Abstract: BackgroundRecently, a simple ECG score (DETERMINE score) has been proposed for estimating myocardial scar in patients with ischaemic cardiomyopathy. We sought to evaluate the usefulness of the DETERMINE score for the assessment of myocardial infarct size (IS) as well as microvascular obstruction (MVO), in the setting of ST-elevation myocardial infarction (STEMI).MethodsThis observational study enrolled 423 patients with STEMI (median age 56, 17% women), revascularised by primary percutaneous coronary intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Lee et al 7 reported that the DETERMINE score estimated infarct size nearly as well as the left ventricular EF (LVEF) measured by CMR. In another study, Tiller et al 15 found a significant positive correlation between the DETERMINE score and MI in patients with STEMI. In our study, a DETERMINE score cut-off of ≤3 had good sensitivity (80.0%) and specificity (74.4%) for predicting MINOCA.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Lee et al 7 reported that the DETERMINE score estimated infarct size nearly as well as the left ventricular EF (LVEF) measured by CMR. In another study, Tiller et al 15 found a significant positive correlation between the DETERMINE score and MI in patients with STEMI. In our study, a DETERMINE score cut-off of ≤3 had good sensitivity (80.0%) and specificity (74.4%) for predicting MINOCA.…”
Section: Discussionmentioning
confidence: 89%
“…Lee et al 7 reported that the DETERMINE score estimated infarct size nearly as well as the left ventricular EF (LVEF) measured by CMR. In another study, Tiller et al 15 Currently, the diagnostic process of MINOCA may require multiple diagnostic steps such as echocardiography, left ventriculography, intracoronary imaging, computed tomography, pulmonary angiography, and CMR. Since there are no practical algorithms for MINOCA, diagnostic tools should be selected according to the suspected etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior STEMI is commonly complicated by hemodynamic deterioration and cardiogenic shock, which in turn carry a high mortality risk. 15 , 16 , 17 A major contributor to morbidity and mortality following an anterior STEMI is adverse cardiac remodelling. 18 The use of the Impella device in selected anterior STEMI patients with shock presentation may improve short-term outcomes, but whether it has a beneficial long-term impact on cardiac remodelling remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to infarct localization, anterior localization seems to be associated with a greater extent of microvascular obstruction and a larger infarct size, which results in a higher incidence of heart failure and adverse events (eg, arrhythmias, secondary mitral regurgitation). 15 , 16 , 17 As a result, we decided to analyze the impact of an Impella device in a selected cohort of patients with anterior localization only, excluding patients with nonanterior infarction.…”
Section: Discussionmentioning
confidence: 99%
“…An ECG was performed before discharge [median: 4 (interquartile range: 2-6) days]. 3 Some scores could be applied in acute or chronic settings; however, a major concern for the present study 1 is the timing of the ECG. The authors 1 reported that an ECG was obtained upon admission.…”
Section: Dear Editormentioning
confidence: 99%